(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To determine the feasibility, safety, efficacy and short term outcome of using new surgical technique for repair of anterior urethral stricture Introduction: The conventional approach for management of long segment anterior urethral stricture is a two stage Johansons repair along with the use of free grafts if required. Now a days the preferred management of urethral stricture involving long segments of anterior urethra is dorsal only oral mucosa Augmentation urethroplasty which requires circumferential mobilization of urthera that might cause ischaemia of urethra in addition of chordee. For that we adopted new technique (kulkarnis) of dorsolateral onlay buccal mucosal graft one sided anterior urethroplasty in which only unilateral urethral mobilization done through perineal approach. Materials and Methods: A total of 50 patients underwent urethroplasty for anterior urethral strictures using dorsolateral onlay BMG from April 2010 to December 2012 at NIKDU, JBFH, BSMMU and BDM Hospital. We selected 16 to 70 years old male (mean age 39 years) underwent a one-sided dorsolateral oral mucosal graft urethroplasty. The mean (range) stricture length was 6.5 (4.5-9) cm in patients with single bulbar urethral involvement and 10.5 (8.5–15.0) cm in patients with panurethral strictures. Free graft was taken from oral mucosa either lower lip or cheeks. Follow up was done by uroflowmetry at 3rd week, after removal of penile catheter and repeat at 3rd and at 6th month. In addition to uroflometry – RGU & MCU was done at 3rd month and Urethrocystoscopy was done at 6th month follow up. The results were classified into the following outcomes. Success was defined as a maximum flow rate of >10 ml/sec, normal RGU, and/or urethroscopy (with a 19 Fr. sheath). Failure was defined as the presence of obstructive urinary tract symptoms, Qmax <10 ml/sec, stricture diagnosed on retrograde urethrogram/ urethroscopy, and the need for any postoperative urethral intervention. Result: The overall follow up was 12-30 months. Of the 50 patients 45 (90%) had a successful outcome and 5(12%) had failure. 3 failure treated by OIU and 2 by meatal dilatation. No significant donor site defect was observed. Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.37-42